Asian development outlook (ADO) 2017 update sustaining development through public-private partnership. (Asian Development Outlook, 2017)
Growth prospects for developing Asia are looking up, bolstered by a revival in world trade and strong momentum in the Peoples Republic of China. Rebounds in international food and fuel prices are gentler than expected, helping to contain consumer price pressures. Inflation is likely to dip to 2.4% in 2017, or 0.1 percentage points off the 2016 rate, and pick up to 2.9% in 2018. Risks to the outlook have become more balanced, as the advanced economies have so far avoided sharp, unexpected changes to their macroeconomic policies. Further, the fuel price rise is providing fiscal relief to oil exporters but is measured enough not to destabilize oil importers.